Simplify the expression below.
3 · -8 + 5 - 4 ÷ 2

(3 * (-8)) + 5 - (4 ÷ 2) = -21

Expert answered|shifa saleheen|Points 9572|

Question|Rated good

Asked 3/23/2012 1:01:41 PM

Updated 2/26/2014 6:46:59 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [2/26/2014 6:46:58 PM], Confirmed by andrewpallarca [2/26/2014 6:46:59 PM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Rating

There are no new answers.

Use the distributive property to find the product of 9 and 23.
**Weegy:** 9 x 23 ~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
(9 x 20) + (9 x 3) ~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
180 + 27 ~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
207 (More)

Question

Expert Answered

Asked 3/22/2012 1:30:44 PM

0 Answers/Comments

Evaluate the expression below.
|8 - 7| · 4 + 3(-1)

Question

Updated 1/25/2018 3:52:15 AM

1 Answer/Comment

|8 - 7| · 4 + 3(-1)

= |1| · 4 + 3(-1)

= 1 · 4 + 3(-1)

= 4 - 3

= 1

= |1| · 4 + 3(-1)

= 1 · 4 + 3(-1)

= 4 - 3

= 1

Added 1/25/2018 3:52:15 AM

This answer has been confirmed as correct and helpful.

what is order of operations for this problem 2 + (3 - 9) ÷ -3 · 4
**Weegy:** Mathematical operation normally follows a specific order which is called MDAS. MDAS stands for Multiplication, Division, Addition and Subtraction. [ Therefore usinf the given problem you need to solve -3 x 4, followed by your (3-9) ÷ -12, and followed by 2 plus the answer on (3 - 9) ÷ -3 x 4. Hence the answer is 4 ] (More)

Question

Expert Answered

Updated 6/24/2014 1:01:53 PM

1 Answer/Comment

2+(3-9)÷-3x4

=2+(3-9)/(0-3)×4

=2+-6/(0-3)×4

=2+-6/-3×4

=2+2×4

=2+8

=10

=2+(3-9)/(0-3)×4

=2+-6/(0-3)×4

=2+-6/-3×4

=2+2×4

=2+8

=10

Added 6/24/2014 1:01:51 PM

This answer has been confirmed as correct and helpful.

what is the order of operations for 2 + (3 - 9) ÷ -3 · 4
**Weegy:** Order of operation including the answer for each operation
1.( -3 x 4) =-12
2. (3-9) =-6
3. (3-9) ÷ (-3 · 4 ) = 2
4. 2+( (3-9) ÷ (-3 · 4 ))
= 2 +2
= 4
4. (More)

Question

Expert Answered

Updated 6/6/2014 1:07:38 PM

1 Answer/Comment

The order of operation for 2 + (3 - 9) ÷ -3 · 4 is PEMDAS, parenthesis, exponent, multiplication or division, addition, and subtraction.

2 + (3 - 9) ÷ -3 · 4;

2 + (-6) ÷ -3 · 4;

2 - 6 ÷ -3 · 4;

2 + 2 · 4;

2 + 8 = 10

2 + (3 - 9) ÷ -3 · 4;

2 + (-6) ÷ -3 · 4;

2 - 6 ÷ -3 · 4;

2 + 2 · 4;

2 + 8 = 10

Added 6/6/2014 1:07:36 PM

This answer has been confirmed as correct and helpful.

Evaluate 8 ÷ -2 · 42 + 9

Question

Updated 6/6/2014 8:31:44 AM

1 Answer/Comment

8 ÷ -2 * 42 + 9;

= -4 * 42 + 9;

= -168 + 9;

= -159

= -4 * 42 + 9;

= -168 + 9;

= -159

Added 6/6/2014 8:31:44 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/6/2014 12:20:15 PM]

37,035,963

questions answered

There are no comments.